Chwila - Łukasiewicz, Jacek (1934-2021).; Szymborska, Wisława (1923-2012). (2002)
Recenzja książki : Chwila / Wisława Szymborska. Kraków, 2002.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.